Asphalt and nano nickel mixed coated negative electrode material and preparation method thereof
Through the preparation method of mixed coated negative electrode materials of asphalt and nano nickel, the problems of poor discharge capacity and low safety of lithium-ion batteries under high and low temperature conditions are solved, and the high rate performance, high temperature resistance and service life of the battery are achieved. promote.
Patent Information
- Application Number
- CN202411587983.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
When the negative electrode materials of existing lithium-ion batteries are used under high and low temperature conditions, the high and low temperature discharge capacity of lithium-ion batteries is poor, the capacity is prone to rapid attenuation, and safety is reduced. In addition, large-scale charging is prone to lithium analysis on the surface of the negative electrode material, resulting in safety problems. .
The preparation method of mixed coated negative electrode material with asphalt and nano nickel is adopted. By mixing the pretreated asphalt with conductive polymer, and ball milling in a ball mill, heating it to a molten state, shearing and stirring evenly, cooling and pulverizing it, and then sphing Graphite, metal nickel and surfactant are mixed and coated, and the negative electrode material is formed after calcination.
Improve the conductivity of the carbon layer, improve the rate performance and high temperature resistance of the battery, extend the service life, and reduce the interfacial tension, so that the modified asphalt and metal nickel are evenly coated on graphite, improving the low temperature resistance of the battery performance.
Smart Images

Figure CN119480967A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and specifically relates to an asphalt and nano-nickel mixed coated negative electrode material and a preparation method thereof. Background Art
[0002] As the number of fuel vehicles continues to grow worldwide, the pressure that vehicles bring to the environment and energy is becoming increasingly severe. New energy vehicles can solve this problem, so they are increasingly valued worldwide. However, new energy vehicles still have many shortcomings, such as short driving range and slow charging speed. In particular, high-rate charging can easily cause lithium deposition on the surface of negative electrode materials, causing serious safety problems. The key to the development of new energy vehicles lies in breakthroughs in battery technology, and the update of battery technology lies in the innovation of materials.
[0003] Graphite has the characteristics of good conductivity, high degree of crystallization, and good layered structure, which makes it very suitable for the embedding and extraction of lithium ions during the charging and discharging process. Therefore, it has become the most widely used negative electrode material. However, the negative electrode material of lithium-ion batteries is currently graphite carbon material. When used under high or low temperature conditions, the high and low temperature discharge capacity of lithium-ion batteries is poor, the capacity is prone to rapid decay, and the safety is greatly reduced. Therefore, it is very important to expand the operating temperature range of lithium-ion batteries and develop negative electrode materials with good temperature resistance.
[0004] Graphite negative electrode materials are generally processed into spherical micropowders. High-end products must go through the coating and carbonization graphitization process. Spherical graphite micropowder coating refers to the use of asphalt, resin, sugar and other polymer materials to wrap the surface of graphite particles, and then directly wrap amorphous carbon through high-temperature carbonization or vapor deposition to form a thin layer of amorphous carbon structure on the surface of spherical graphite micropowders to improve the initial efficiency and cycle performance of lithium-ion batteries.
[0005] There are three methods for coating spherical graphite powder with asphalt, namely solid phase mixing, liquid phase mixing and gas phase deposition. Liquid phase mixing is more commonly used. When coating with liquid phase mixing, asphalt is dissolved in an organic solvent and then mixed. After high temperature treatment, the solvent is evaporated to form an intermediate phase asphalt, which is then used to coat the graphite, remove light asphalt and solvent, and then carbonize to form coated carbon on the surface of carbon particles.
[0006] Therefore, there is an urgent need for an asphalt and nano-nickel mixed coated negative electrode material and a preparation method thereof. Summary of the invention
[0007] The purpose of the present invention is to provide a bitumen and nano-nickel mixed coated negative electrode material and a preparation method thereof.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] A method for preparing a mixed asphalt and nano-nickel coated negative electrode material, the preparation method comprising the following steps:
[0010] (1) Asphalt pretreatment: After the asphalt is crushed, it is passed through a 200-300 mesh sieve. The sieved material is taken, and water 6-8 times the mass of the asphalt is added, mixed evenly, and added to a sand mill for grinding. When the D50 is 2-4 μm, the grinding is completed, filtered, and dried to obtain pretreated asphalt;
[0011] (2) Asphalt modification: pretreated asphalt and polymer are mixed in a mass ratio of (30-35):1, added into a ball mill, ball milled at a speed of 400-600 rpm for 5-7 hours, then heated to a molten state, sheared and stirred evenly, and crushed after cooling to obtain modified asphalt;
[0012] (3) adding 1 part by mass of spherical graphite to a coating machine, adding 3-5 parts by mass of alcohol and 0.03-0.06 parts by mass of a surfactant, stirring at 500-700 rpm, continuing to add 0.4-0.6 parts by mass of modified asphalt, stirring at 1000-1500 rpm, and then adding 0.1-0.3 parts by mass of metallic nickel, and continuing to stir at 1000-1500 rpm to obtain a mixture;
[0013] (4) Calcine the mixture under a nitrogen atmosphere, first heating the mixture to 90-95°C at a rate of 2-5°C / min and keeping the temperature for 1-2 hours; then heating the mixture to 900-950°C at a rate of 6-10°C / min and keeping the temperature for 2-3 hours; finally heating the mixture to 1300-1350°C at a rate of 12-15°C / min and keeping the temperature for 1-2 hours; then cool the mixture to room temperature to obtain the negative electrode material.
[0014] Furthermore, the D50 of the spherical graphite is between 10-15 μm and the tap density is 0.95-1.01 g / cm 3 .
[0015] Furthermore, the polymer is selected from one or more of polyaniline, 3-octyl-substituted polythiophene, and polypyrrole.
[0016] Furthermore, the polymer is a mixture of polyaniline, 3-octyl substituted polythiophene and polypyrrole in a mass ratio of 1:(1.3-1.5):(0.4-0.6).
[0017] The present invention uses three kinds of conductive polymer modified asphalt, and utilizes its conductivity and electrochemical properties to improve the conductivity of the carbon layer. At the same time, since part of the conductive polymer volatilizes during calcination, on the basis of the material structure formed by asphalt, metal nickel and graphite, the volatilization of the polymer can further form a carbon layer with certain carbon micropores, thereby improving the density of the negative electrode material, increasing the lithium insertion speed and reserves, improving the rate performance and high temperature resistance of the battery, and increasing the service life.
[0018] Polyaniline was purchased from MacLean, catalog number P824522.
[0019] 3-Octyl substituted polythiophene was purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number Y19320
[0020] Polypyrrole was purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number T25300.
[0021] Furthermore, the metal nickel has a mass ratio of 1: (1.4-1.6): (0.2-0.5) with an average particle size of 20nm and a specific surface area of 14m 2 / g of metallic nickel, an average particle size of 50nm, and a specific surface area of 12m 2 / g of metallic nickel and an average particle size of 80nm and a specific surface area of 11m 2 / g of metallic nickel mixture. Purchased from Jinlei Technology.
[0022] Furthermore, the surfactant is sodium dodecyl sulfate, Tween 60 and a homemade surfactant in a mass ratio of 1: (0.2-0.5): (1.3-1.6).
[0023] Furthermore, the preparation method of the homemade surfactant comprises the following steps, measured by weight:
[0024] S1: Add 150 parts of lauryl alcohol and 5-7 parts of potassium hydroxide to a stainless steel reactor, maintain the temperature at 30-35°C, evacuate the reactor, raise the temperature to 110-115°C, add 1730-1740 parts of alkylene oxide, add it within 7-9 hours, control the pressure at 0.1-0.3MPa, the temperature at 115-120°C, react for 3-5 hours, and obtain polyether polyol;
[0025] S2: Add 900 parts of polyether polyol and 1220-1240 parts of glycerol into a stainless steel reactor. After the reactor is replaced with nitrogen, the temperature is raised to 142-146°C and the pressure in the reactor is filled to 0.1-0.3MPa. When the pressure in the reactor drops, the temperature is controlled at 115-120°C and the pressure at 0.2-0.4MPa. The reaction is carried out for 6-8h to obtain a homemade surfactant.
[0026] Furthermore, the alkylene oxide is a mixture of ethylene oxide, propylene oxide and 2,3-butylene oxide in a mass ratio of (0.5-0.8):1:(1.2-1.4).
[0027] The self-made surfactant in the compounded surfactant used in the present invention retains part of the hydroxyl group and has a repeating alkane group. After being compounded with sodium dodecyl sulfate and Tween 60, the interfacial tension between graphite, asphalt and metallic nickel can be better reduced, and the modified asphalt and metallic nickel can be evenly coated on the graphite, thereby improving the rate and low temperature resistance of the battery.
[0028] Furthermore, the softening point of the asphalt is less than 95°C.
[0029] Furthermore, the softening point of the modified asphalt is 90-95°C.
[0030] The invention also provides an asphalt and nano-nickel mixed coated negative electrode material obtained by the preparation method.
[0031] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0032] 1. The present invention mixes and coats spherical graphite, modified asphalt and metal nickel in solvent alcohol, stirs and extrude uniformly, and can pressurize metal nickel into the gaps of graphite. At the same time, the spherical graphite particles are changed into flakes, and the metal nickel is coated on the graphite by asphalt modification. The battery prepared by the negative electrode material prepared by the present invention has excellent electrical performance, good low temperature resistance and high temperature resistance, and has broad market prospects.
[0033] 2. The present invention uses three types of conductive polymer modified asphalt, and utilizes its conductivity and electrochemical properties to improve the conductivity of the carbon layer, improve the rate performance and high temperature resistance of the battery, and increase the service life.
[0034] 3. The present invention uses a compounded surfactant, which can better reduce the interfacial tension between graphite, asphalt and metallic nickel, and can make the modified asphalt and metallic nickel evenly coated on the graphite, thereby improving the rate performance and low temperature resistance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a resistivity test diagram of the negative electrode material of Example 1.
[0036] Figure 2 This is a backscattered light reference spectrum of the negative electrode slurry prepared using the negative electrode material of Example 1.
[0037] Figure 3 This is a transmitted light reference spectrum of the negative electrode slurry prepared using the negative electrode material of Example 1.
[0038] Figure 4This is a SEM test image of a negative electrode sheet prepared using the negative electrode material prepared in Example 1. DETAILED DESCRIPTION
[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] This embodiment provides a method for preparing a mixed asphalt and nano-nickel coated negative electrode material, the preparation method comprising the following steps:
[0042] (1) Asphalt pretreatment: After the asphalt is crushed, it is passed through a 200-mesh sieve. The sieve material is taken, and water 7 times the mass of the asphalt is added. The mixture is mixed evenly and added to a sand mill for grinding. The grinding is completed when D50 is 3 μm. The asphalt is filtered and dried to obtain pretreated asphalt. The asphalt in this embodiment is ordinary medium-temperature coal tar with a softening point of 90.2°C.
[0043] (2) Asphalt modification: pretreated asphalt and polymer were mixed at a mass ratio of 32:1, added into a ball mill, and ball milled at a speed of 500 rpm for 6 h, then heated to a molten state, sheared and stirred evenly, and crushed after cooling to obtain modified asphalt;
[0044] (3) adding 1 part by mass of spherical graphite to a coating machine, adding 4 parts by mass of alcohol and 0.05 parts by mass of a surfactant, stirring at 600 rpm, continuing to add 0.5 parts by mass of modified asphalt, stirring at 1200 rpm, and then adding 0.2 parts by mass of metallic nickel, continuing to stir at 1200 rpm to obtain a mixture;
[0045] (4) The mixture was calcined in a nitrogen atmosphere, first by heating to 92°C at a rate of 4°C / min and keeping the temperature for 1.5 h; then by heating to 920°C at a rate of 8°C / min and keeping the temperature for 2.6 h; finally, by heating to 1320°C at a rate of 14°C / min and keeping the temperature for 1.4 h; then, the temperature was cooled to room temperature to obtain the negative electrode material.
[0046] The D50 of the spherical graphite is 12 μm and the tap density is 0.97 g / cm 3 .
[0047] The polymer is a mixture of polyaniline, 3-octyl substituted polythiophene and polypyrrole in a mass ratio of 1:1.4:0.5.
[0048] Polyaniline was purchased from MacLean, catalog number P824522.
[0049] 3-Octyl substituted polythiophene was purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number Y19320
[0050] Polypyrrole was purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number T25300.
[0051] The metal nickel has a mass ratio of 1:1.5:0.3, an average particle size of 20nm, and a specific surface area of 14m 2 / g of metallic nickel, an average particle size of 50nm, and a specific surface area of 12m 2 / g of metallic nickel and an average particle size of 80nm and a specific surface area of 11m 2 / g of metallic nickel mixture. Purchased from Jinlei Technology.
[0052] The surfactant is sodium dodecyl sulfate, Tween 60 and a homemade surfactant in a mass ratio of 1:0.4:1.5.
[0053] The preparation method of the homemade surfactant comprises the following steps by weight:
[0054] S1: Add 150 parts of lauryl alcohol and 6 parts of potassium hydroxide into a stainless steel reactor, keep the temperature at 32°C, evacuate the reactor, raise the temperature to 112°C, add 1735 parts of alkylene oxide, add it within 8 hours, control the pressure at 0.2MPa, the temperature at 117°C, react for 4 hours, and obtain polyether polyol;
[0055] S2: Add 900 parts of polyether polyol and 12230 parts of glycerol into a stainless steel reactor. After the reactor is replaced with nitrogen, the temperature is raised to 144°C and the pressure in the reactor is filled to 0.2MPa. When the pressure in the reactor drops, the temperature is controlled at 117°C and the pressure is 0.3MPa. The reaction is carried out for 7 hours to obtain a homemade surfactant.
[0056] The alkylene oxide is a mixture of ethylene oxide, propylene oxide and 2,3-butylene oxide in a mass ratio of 0.7:1:1.3.
[0057] Example 2
[0058] This embodiment provides a method for preparing a mixed asphalt and nano-nickel coated negative electrode material, the preparation method comprising the following steps:
[0059] (1) Asphalt pretreatment: After the asphalt is crushed, it is passed through a 200-mesh sieve. The sieve material is taken, and water 6 times the mass of the asphalt is added. The mixture is mixed evenly and then added to a sand mill for grinding. The grinding is completed when D50 is 2 μm. The asphalt is filtered and dried to obtain pretreated asphalt. The asphalt in this embodiment is ordinary medium-temperature coal tar with a softening point of 90.2°C.
[0060] (2) Asphalt modification: pretreated asphalt and polymer were mixed at a mass ratio of 30:1, added into a ball mill, and ball milled at 400 rpm for 5 h. The mixture was then heated to a molten state, sheared and stirred to obtain a modified asphalt after cooling.
[0061] (3) adding 1 part by mass of spherical graphite to a coating machine, adding 3 parts by mass of alcohol and 0.03 parts by mass of a surfactant, stirring at 500 rpm, adding 0.4 parts by mass of modified asphalt, stirring at 1000 rpm, adding 0.1 parts by mass of metallic nickel, and stirring at 1000 rpm to obtain a mixture;
[0062] (4) The mixture was calcined in a nitrogen atmosphere by first heating the mixture to 90°C at a rate of 2°C / min and keeping the temperature for 1 h; then heating the mixture to 900°C at a rate of 6°C / min and keeping the temperature for 3 h; finally heating the mixture to 1300°C at a rate of 12°C / min and keeping the temperature for 2 h; then cooling the mixture to room temperature to obtain the negative electrode material.
[0063] The D50 of the spherical graphite is 12 μm and the tap density is 0.97 g / cm 3 .
[0064] The polymer is a mixture of polyaniline, 3-octyl substituted polythiophene and polypyrrole in a mass ratio of 1:1.3:0.4.
[0065] Polyaniline was purchased from MacLean, catalog number P824522.
[0066] 3-Octyl substituted polythiophene was purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number Y19320
[0067] Polypyrrole was purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number T25300.
[0068] The metal nickel has a mass ratio of 1:1.4:0.5, an average particle size of 20nm, and a specific surface area of 14m 2 / g of metallic nickel, an average particle size of 50nm, and a specific surface area of 12m 2 / g of metallic nickel and an average particle size of 80nm and a specific surface area of 11m 2 / g of metallic nickel mixture. Purchased from Jinlei Technology.
[0069] The surfactant is sodium dodecyl sulfate, Tween 60 and a homemade surfactant in a mass ratio of 1:0.2:1.3.
[0070] The preparation method of the homemade surfactant comprises the following steps by weight:
[0071] S1: Add 150 parts of lauryl alcohol and 5 parts of potassium hydroxide into a stainless steel reactor, keep the temperature at 30°C, evacuate the reactor, heat it to 110°C, add 1730 parts of alkylene oxide, add it within 7 hours, control the pressure at 0.1 MPa and the temperature at 115°C, react for 3 hours, and obtain polyether polyol;
[0072] S2: Add 900 parts of polyether polyol and 1220 parts of glycerol into a stainless steel reactor. After the reactor is replaced with nitrogen, the temperature is raised to 142°C and the pressure in the reactor is filled to 0.1 MPa. When the pressure in the reactor drops, the temperature is controlled at 115°C and the pressure is 0.2 MPa. The reaction is carried out for 6 hours to obtain a homemade surfactant.
[0073] The alkylene oxide is a mixture of ethylene oxide, propylene oxide and 2,3-butylene oxide in a mass ratio of 0.5:1:1.2.
[0074] Comparative Example 1
[0075] The difference between this comparative example and Example 1 is that the grinding is completed when D50 is 10 μm, and the asphalt is filtered and dried to obtain the pretreated asphalt.
[0076] Comparative Example 2
[0077] The difference between this comparative example and Example 1 is that the D50 of the spherical graphite is between 25 μm and the tap density is 0.91 g / cm 3 .
[0078] Comparative Example 3
[0079] The difference between this comparative example and Example 1 is that the polymer is a mixture of polyaniline, 3-octyl-substituted polythiophene and polypyrrole in a mass ratio of 1:1:1.
[0080] Comparative Example 4
[0081] The difference between this comparative example and Example 1 is that the metal nickel is in a mass ratio of 1:1:1, with an average particle size of 20nm and a specific surface area of 14m 2 / g of metallic nickel, an average particle size of 50nm, and a specific surface area of 12m 2 / g of metallic nickel and an average particle size of 80nm and a specific surface area of 11m 2 / g of metallic nickel mixture. Purchased from Jinlei Technology.
[0082] Comparative Example 5
[0083] The difference between this comparative example and Example 1 is that the metal nickel is in a mass ratio of 1:1.5:0.3, with an average particle size of 100 nm and a specific surface area of 9.8 m 2 / g of metallic nickel, an average particle size of 200nm, and a specific surface area of 8.5m 2 / g of metallic nickel and an average particle size of 300nm and a specific surface area of 8.2m 2 / g of metallic nickel mixture. Purchased from Jinlei Technology.
[0084] Comparative Example 6
[0085] The difference between this comparative example and Example 1 is that the surfactant is sodium dodecyl sulfate, Tween 60 and a homemade surfactant in a mass ratio of 1:1:1.
[0086] The preparation method of the homemade surfactant comprises the following steps by weight:
[0087] S1: Add 150 parts of lauryl alcohol and 6 parts of potassium hydroxide into a stainless steel reactor, keep the temperature at 32°C, evacuate the reactor, raise the temperature to 112°C, add 1735 parts of alkylene oxide, add it within 8 hours, control the pressure at 0.2MPa, the temperature at 117°C, react for 4 hours, and obtain polyether polyol;
[0088] S2: Add 900 parts of polyether polyol and 12230 parts of glycerol into a stainless steel reactor. After the reactor is replaced with nitrogen, the temperature is raised to 144°C and the pressure in the reactor is filled to 0.2MPa. When the pressure in the reactor drops, the temperature is controlled at 117°C and the pressure is 0.3MPa. The reaction is carried out for 7 hours to obtain a homemade surfactant.
[0089] Comparative Example 7
[0090] The difference between this comparative example and Example 1 is that the alkylene oxide is a mixture of ethylene oxide, propylene oxide and 2,3-butylene oxide in a mass ratio of 1:1:1.
[0091] Performance Testing
[0092] The negative electrode materials of Examples 1-2 and Comparative Examples 1-7 were used as samples, and batteries were assembled according to the ratio (mass ratio) in Table 1.
[0093] Table 1 Battery Ratio
[0094]
[0095] 1. Evaluation of negative electrode materials
[0096] The compaction density of the negative electrode material prepared in Example 1 is 2.005 g / cm 3 , the change of resistivity and pressure is as follows Figure 1 As shown, through Figure 1 It can be seen that the resistivity decreases with increasing pressure and tends to be stable after 50 MPa. The resistivity is 0.0023Ω·cm at 60 MPa.
[0097] 2. Negative electrode slurry performance
[0098] pass Figure 2-3 It can be seen that the 24h stability change of the negative electrode slurry prepared by the negative electrode material of Example 1 is 0.5%, and the slurry stability is good.
[0099] 3. Negative electrode performance test
[0100] The SEM image of the negative electrode obtained in Example 1 is shown in Figure 4 From the SEM results, it can be seen that the negative electrode has distinct microscopic morphology and particles are adhered to each other after charging and discharging.
[0101] 4. The electrical performance of the batteries prepared using the negative electrode materials of Examples 1-2 and Comparative Examples 1-7 was tested with reference to GB / T24533-2019. The results are shown in Table 2.
[0102] Table 2 Electrical performance test results
[0103]
[0104] It can be seen from Table 1 that the batteries prepared with the negative electrode materials of Examples 1-2 have excellent electrical properties, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect between the raw materials.
[0105] In Comparative Examples 1-2, the particle size of the pretreated asphalt and the particle size of the spherical graphite were changed, and it can be seen that the performance of the battery decreased, proving that the particle sizes of the two raw materials affect the performance of the battery. In Comparative Example 3, the polymer ratio was changed, and it can be seen from the results that the high temperature resistance of the battery was affected. The different parameter ratios of nickel in Comparative Examples 4-5 will also affect the performance of the battery. From Comparative Examples 6-7, it can be seen that the change of the surfactant will reduce the low temperature resistance of the battery. The above experimental results further prove the importance of the technical scheme defined in the present invention for its technical effects.
[0106] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a mixed asphalt and nano-nickel coated negative electrode material, characterized in that: The preparation method comprises the following steps: (1) Asphalt pretreatment: After the asphalt is crushed, it is passed through a 200-300 mesh sieve. The sieved material is taken, and water 6-8 times the mass of the asphalt is added, mixed evenly, and added to a sand mill for grinding. When the D50 is 2-4 μm, the grinding is completed, filtered, and dried to obtain pretreated asphalt; (2) Asphalt modification: pretreated asphalt and polymer are mixed in a mass ratio of (30-35):1, added into a ball mill, ball milled at a speed of 400-600 rpm for 5-7 hours, then heated to a molten state, sheared and stirred evenly, and crushed after cooling to obtain modified asphalt; (3) adding 1 part by mass of spherical graphite to a coating machine, adding 3-5 parts by mass of alcohol and 0.03-0.06 parts by mass of a surfactant, stirring evenly, continuing to add 0.4-0.6 parts by mass of modified asphalt, stirring evenly, and then adding 0.1-0.3 parts by mass of metallic nickel, continuing to stir evenly, to obtain a mixture; (4) Calcine the mixture under a nitrogen atmosphere, first heating the mixture to 90-95°C at a rate of 2-5°C / min and keeping the temperature for 1-2 hours; then heating the mixture to 900-950°C at a rate of 6-10°C / min and keeping the temperature for 2-3 hours; finally heating the mixture to 1300-1350°C at a rate of 12-15°C / min and keeping the temperature for 1-2 hours; then cool the mixture to room temperature to obtain the negative electrode material.
2. The method for preparing the asphalt and nano-nickel mixed coated negative electrode material according to claim 1, characterized in that: The D50 of the spherical graphite is between 10-15 μm and the tap density is 0.95-1.01 g / cm 3 .
3. The method for preparing the asphalt and nano-nickel mixed coated negative electrode material according to claim 1, characterized in that: The polymer is selected from one or more of polyaniline, 3-octyl substituted polythiophene and polypyrrole.
4. The method for preparing the asphalt and nano-nickel mixed coated negative electrode material according to claim 3, characterized in that: The polymer is a mixture of polyaniline, 3-octyl substituted polythiophene and polypyrrole in a mass ratio of 1: (1.3-1.5): (0.4-0.6).
5. The method for preparing the asphalt and nano-nickel mixed coated negative electrode material according to claim 1, characterized in that: The metal nickel has a mass ratio of 1: (1.4-1.6): (0.2-0.5) with an average particle size of 20nm and a specific surface area of 14m 2 / g of metallic nickel, an average particle size of 50nm, and a specific surface area of 12m 2 / g of metallic nickel and an average particle size of 80nm and a specific surface area of 11m 2 / g of metallic nickel mixed.
6. The method for preparing the asphalt and nano-nickel mixed coated negative electrode material according to claim 1, characterized in that: The surfactant is a mixture of sodium dodecyl sulfate, Tween 60 and a self-made surfactant in a mass ratio of 1: (0.2-0.5): (1.3-1.6).
7. The method for preparing the asphalt and nano-nickel mixed coated negative electrode material according to claim 6, characterized in that: The preparation method of the homemade surfactant comprises the following steps by weight: S1: Add 150 parts of lauryl alcohol and 5-7 parts of potassium hydroxide to a stainless steel reactor, maintain the temperature at 30-35°C, evacuate the reactor, raise the temperature to 110-115°C, add 1730-1740 parts of alkylene oxide, add it within 7-9 hours, control the pressure at 0.1-0.3MPa, the temperature at 115-120°C, react for 3-5 hours, and obtain polyether polyol; S2: Add 900 parts of polyether polyol and 1220-1240 parts of glycerol into a stainless steel reactor. After the reactor is replaced with nitrogen, the temperature is raised to 142-146°C and the pressure in the reactor is filled to 0.1-0.3MPa. When the pressure in the reactor drops, the temperature is controlled at 115-120°C and the pressure at 0.2-0.4MPa. The reaction is carried out for 6-8h to obtain a homemade surfactant.
8. The method for preparing the asphalt and nano-nickel mixed coated negative electrode material according to claim 1, characterized in that: The alkylene oxide is a mixture of ethylene oxide, propylene oxide and 2,3-butylene oxide in a mass ratio of (0.5-0.8):1:(1.2-1.4).
9. The method for preparing the asphalt and nano-nickel mixed coated negative electrode material according to claim 1, characterized in that: The softening point of the modified asphalt is 90-95°C.
10. A mixed asphalt and nano-nickel coated negative electrode material obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of graphite negative electrode material containing hollow carbon nanostructure for lithium ion battery
CN102867945A
TiO2 / C coated graphite composite material, preparation method and application thereof as lithium ion battery negative electrode material
CN105762340A
Electrode active material, electrode and secondary battery including the same, and method of preparing the electrode active material
CN106953068A
Modified asphalt coated microcrystalline graphite negative electrode material and preparation method thereof
CN115579470A
Nano-doped asphalt coated graphite material as well as preparation method and application thereof
CN116072842A